Intraoperative Disinfection by Pulse Irrigation with Povidone-Iodine Solution in Spine Surgery - Vincenzo De Luna; Federico Mancini; Fernando De Maio; Gabriele Bernardi; Ernesto Ippolito; Roberto Caterini (Advances in Orthopedics)
Background. Deep wound infection in spine surgery is a debilitating complication for patients and increases costs. The objective of this prospective study was to evaluate the efficacy of wound pulse irrigation with a dilute povidone-iodine solution in the prevention of surgical site infection. Methods. 50 patients undergoing spinal surgery were randomly divided into two groups (A and B) of 25 patients each. In group A, wounds were irrigated with dilute (3%) povidone-iodine solution through a low-pressure pulsatile device. In group B, wounds were irrigated with saline solution through a bulb syringe. In both groups, specimens for bacterial culture were harvested from surgical site before and after irrigation. Results. In group A, no surgical site infection occurred; in group B, deep wound infection was observed in 3 patients. In both groups, before irrigation some cultures have been found positive for bacterial contamination. Conclusion. Our study seems to support the idea that low-pressure pulsating lavage of surgical wounds with povidone-iodine diluted to a nontoxic concentration of 3% is an effective therapeutic adjunct measure to prevent surgical site infection in spine surgery. However, the number of the enrolled patients is small and a significant statistical analysis is not practicable. This trial is registered with NCT03249363.